OPTIMALISASI PERAN DAN FUNGSI GURU BIMBINGAN DAN KONSELING DALAM IMPLEMENTASI KURIKULUM 13 - Nurhayati, Nanik; Pw, Siti Nurfarida (Jurnal Bikotetik (Bimbingan dan Konseling : Teori dan Praktik), 2019)
In order to optimize the role and function of Teacher Guidance and Counseling in schools, it is necessary to socialize the understanding and understanding of several policies that contain the role and function of the Guidance and Counseling / Counselor Teachers to the school components and abort the assumption that the Guidance and Counseling teachers only help to solve the problematic counselees and also some Guidance and Counseling Teachers / Counselors who have not understand abouth her/his the role and function. In order to optimize the role and function of Guidance and Counseling / Counselor Teachers; there are several things that must be done such as; 1. to enrichment the role; 2. have to show the professionalism well; 3. help the students to choose and to establish the ˜interest and ideamprefessionally; 4. having a high commitment in effort to improve their qualifications and abilities to achieve the specified professional standards.